Exploring spirituality’s location in sustainable clothing consumption through “Black Swan” narratives - Joyner Martinez, Cosette M. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
“Black swan” events (e.g., pandemics, natural disasters, war) often prompt individuals to clarify their self-concept and boost self-esteem with consumptive activities when their mortality is threatened. Research about the Covid-19 pandemic’s effects on clothing consumption indicates that some consumers shifted toward more conscious clothing consumption habits, which may be associated with a desire for self-transcendence (e.g., spirituality). The purpose of this study was to locate spirituality’s role in consumption practice that strengthens clothing’s longevity. Narrative inquiry methodology was used to engage individuals who reported a spiritual experience relevant to their consumption during the pandemic. The study explores the nature of narrators’ spiritual experiences, insights, and the clothing consumption practices and ideals that are informed by each narrator’s spiritual framework, which is idiosyncratic and deeply personal. The pandemic is described by narrators in this study as an opportunity for personal growth and insight into the value of time and relationships. Narrators describe an increased spiritual consciousness, leading to a sense of interconnectedness and responsibility, beyond their own survival. Their empathy for others expands. Materiality is reevaluated in their spiritual sense of what makes a "good life." Most importantly, narrators squarely negotiate their identity through contemplative spiritual practices and reduce their need for external approval. This allows them to deepen their commitment to reduce or restrain their clothing consumption habits. The narrators illustrate how sustainable clothing consumption is itself a spiritual practice that results in greater freedom of expression and a more meaningful and satisfying experience with clothing.